Perceptions of graduates on the development of clinical competence in nursing training (Research, Society and Development, 2021)
Descriptive, exploratory study with a qualitative approach, which aimed to understand the perception of nursing graduates about the development of clinical competence during graduation, and how they perceive themselves able to exercise it as nurses. The results were presented based on three main themes: 1) Constituent elements of clinical competence and its development during the graduation; 2) Dichotomies in the teaching-learning process and implications for the development of clinical competence; and 3) Teacher-Student Interaction in the development of clinical competence. Discussions of the themes focused on the need for articulation between theory and practice through the early insertion of students in practical scenarios, the importance of supervised internships and their power for the mobilization of knowledge and the impacts of interpersonal interactions and evaluation processes for the development of clinical competence in nursing students. The study made it possible to understand the pressing need for educational institutions to think about the training of students integrated with practical scenarios, by highlighting the importance of bringing the student closer to the nurse assistance. In the training process, students see the teacher and preceptor as a reference to be mimicked, and for that, they need the relationship to be permeated by respect, encouragement and empathy.